A critical genetic interaction between Gemin3/Ddx20 and translation initiation factor NAT1/eIF4G2 drives development. - Cacciottolo, R.; Cauchi, R.J. (Developmental Biology, 2025)
Gemin3 (Gem3) or DEAD-box RNA helicase 20 (Ddx20) has been mostly implicated in the assembly of spliceosomal small nuclear ribonucleoproteins (snRNPs) as part of the SMN-Gemins complex. Nonetheless, several studies have hinted at its participation in diverse snRNP-independent activities. Here, we utilised a narrow unbiased genetic screen to discover novel Gem3 interactors in Drosophila with the aim of gaining better insights on its function in vivo. Through this approach, we identified a novel genetic interaction between Gem3 and NAT1, which encodes the Drosophila orthologue of translational regulator eIF4G2. Despite lack of a physical association, loss of NAT1 function was found to downregulate Gem3 mRNA levels. Extensive convergence in transcriptome alterations downstream of Gem3 and NAT1 silencing further supports a functional relationship between these factors in addition to showing a requirement for both in actin cytoskeleton organisation and organism development, particularly neurodevelopment. In confirmation, flies with either Gem3 or NAT1 depletion exhibited brain growth defects and reduced muscle contraction. Severe delays in developmental progression were also observed in a newly generated Gem3 hypomorphic mutant. Our data linking Gemin3 to a key component of the translational machinery support an emerging role for Gemin3 in translation that is also critical during organism development.